2016
DOI: 10.1103/physrevb.93.094428
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of a stable half-metal ferromagnetic BaCl solid

Abstract: Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiquez avec nous à PublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. Questions? Contact the NRC Publications Archive team atPublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. If you wish to email the authors directly, please see the first page of the pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…As a consequence, in contrast to the pristine monolayer, the case with a Cr vacancy shows HM nature in both GGA and GGA+U methods(Figure e,d). Local structure change induced electronic variation is important in discovering half metal and similar transition is found in other cases such as BaCl …”
Section: Structure Parameters For Bulk (C2/m and R‐3) And Crcl3 Monolmentioning
confidence: 99%
“…As a consequence, in contrast to the pristine monolayer, the case with a Cr vacancy shows HM nature in both GGA and GGA+U methods(Figure e,d). Local structure change induced electronic variation is important in discovering half metal and similar transition is found in other cases such as BaCl …”
Section: Structure Parameters For Bulk (C2/m and R‐3) And Crcl3 Monolmentioning
confidence: 99%
“…More interestingly, Ba in pressure-induced fluorides shows the attribute of 5p-elements . However, Ba with a 5d occupation in compounds is rather rare. , If these compounds exist, they might exhibit superconductivity and magnetism.…”
mentioning
confidence: 99%
“…The previous study on LaMnO 3 indicated that uniaxial pressure leads to nearly degenerate e g states instead of a Jahn–Teller (JT) distortion because uniaxial pressure initiates a structural phase transition . A recent study on BaCl also reported a half metallic state introduced by a structure transition . In Fe 0.5 Cr 0.5 F 2 , although orthorhombic symmetry is remained, finite changes in structure take place under uniaxial pressure.…”
Section: Resultsmentioning
confidence: 98%